Vasodepressor Effects of Adenosine in the Cat are Independent of Cyclooxygenase, Potassium Channels, and Nitric Oxide Pathways - Alan David Kaye; Syed R. Baber; Mohammed T. Sharief; Rachel J. Kaye; Elyse M. Cornett (Adis, Springer Healthcare, 2019)
Abstract Background Pulmonary arterial hypertension is a hemodynamic disorder. Signs and symptoms are generally difficult to recognize because they are non-specific. The current treatment for pulmonary arterial hypertension offers no cure or prevention; therefore, it is important to explore treatment avenues for novel pulmonary arterial hypertension treatments. In this study, we tested the hypothesis: pulmonary vasodilator responses of adenosine are dependent on the activation of l-type calcium channels, independent of the synthesis of nitric oxide from l-arginine, activation of adenosine triphosphate-sensitive potassium channels, and the release of cyclooxygenase products. Methods We performed an isolated lobar lung preparation in mongrel cats. The thromboxane A2 analog U-46619 was used to increase lobar arterial pressure to a high steady level. We recorded responses to adenosine and other vasodepressor agents in the pulmonary vascular bed of a cat under conditions of controlled pulmonary blood flow and constant left atrial pressure. Results These data show that adenosine has significant vasodepressor activity in the pulmonary vascular bed of the cat. The data suggest that pulmonary vasodilator responses to adenosine are partially dependent on the activation of adenosine 1 and 2 receptor pathways, and independent of the activation of cyclooxygenase activation, adenosine triphosphate-sensitive K + channels, or synthesis of nitric oxide in the pulmonary vascular bed of the cat. Conclusions Vasodepressor effects of adenosine are species specific, and this species specificity will impact the development of future testing and treatments for pulmonary arterial hypertension. Clinical studies are warranted to see if adenosine moieties could play a therapeutic role in patients with pulmonary arterial hypertension and/or other pulmonary pathogeneses.